Gustatory and olfactory feeding responces in Japanese koi carp (Cyprinus carpio) - Barnard, Philip (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Animal Sciences. Aquaculture))--University of Stellenbosch, 2006.